The Impact of Work Experience, Knowledge, and Motivation on Cadre Performance in Stunting Prevention in Malang District - Rifzul Maulina; Anik Sri Purwanti; Dian Pitaloka Priasmoro (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Stunting is a critical issue that can be addressed through various interventions, one of which involves the active participation of community cadres. This study aimed to assess the role of knowledge and motivation as mediating factors between the duration of service as a cadre and their performance in the stunting prevention program at the Tajinan and Wagir Health Centers. The research used an analytic observational study design with a cross-sectional approach. The study population consisted of 608 cadres across two health centers, and a sample of 125 cadres from each health center was selected using proportional cluster random sampling. To analyze the data, an Independent Sample T-Test was used to compare the duration of service as a cadre, knowledge, motivation, and performance between the two health centers. Path analysis was conducted to explore the impact of the duration of service as a cadre on performance, mediated by knowledge and motivation. The results indicated that there were significant differences in the knowledge and performance of the cadres, while the duration of service and motivation did not show significant differences between the two health centers. Path analysis revealed that knowledge and motivation were not significant mediators in the relationship between the duration of service and cadre performance. Furthermore, the length of time as a cadre did not significantly impact performance in either health center. However, motivation emerged as the most influential factor, with a substantial effect on the performance of the cadres in both health centers. Based on these findings, it is recommended that stunting prevention programs focus on enhancing the motivation of cadres to improve their performance, rather than solely relying on the duration of their service or their knowledge levels.